Anti-Inflammatory and Pro-Autophagy Effects of the Cannabinoid Receptor CB2R: Possibility of Modulation in Type 1 Diabetes - Liu, Qing-Rong; Aseer, Kanikkai Raja; Yao, Qin; Zhong, Xiaoming; Ghosh, Paritosh; O’Connell, Jennifer F.; Egan, Josephine M. (Frontiers in Pharmacology, 2022)
Type 1 diabetes mellitus (T1DM) is an autoimmune disease resulting from loss of insulin-secreting ß-cells in islets of Langerhans. The loss of ß-cells is initiated when self-tolerance to ß-cell-derived contents breaks down, which leads to T cell-mediated ß-cell damage and, ultimately, ß-cell apoptosis. Many investigations have demonstrated the positive effects of antagonizing cannabinoid receptor 1 (CB1R) in metabolic diseases such as fatty liver disease, obesity, and diabetes mellitus, but the role of cannabinoid receptor 2 (CB2R) in such diseases is relatively unknown. Activation of CB2R is known for its immunosuppressive roles in multiple sclerosis, rheumatoid arthritis, Crohn’s, celiac, and lupus diseases, and since autoimmune diseases can share common environmental and genetic factors, we propose CB2R specific agonists may also serve as disease modifiers in diabetes mellitus. The CNR2 gene, which encodes CB2R protein, is the result of a gene duplication of CNR1, which encodes CB1R protein. This ortholog evolved rapidly after transitioning from invertebrates to vertebrate hundreds of million years ago. Human specific CNR2 isoforms are induced by inflammation in pancreatic islets, and a CNR2 nonsynonymous SNP (Q63R) is associated with autoimmune diseases. We collected evidence from the literature and from our own studies demonstrating that CB2R is involved in regulating the inflammasome and especially release of the cytokine interleukin 1B. Furthermore, CB2R activation controls intracellular autophagy and may regulate secretion of extracellular vesicles from adipocytes that participate in recycling of lipid droplets, dysregulation of which induces chronic inflammation and obesity. CB2R activation may play a similar role in islets of Langerhans. Here, we will discuss future strategies to unravel what roles, if any, CB2R modifiers potentially play in T1DM.